2015
DOI: 10.1186/s12920-015-0085-1
|View full text |Cite
|
Sign up to set email alerts
|

The DNA methylation drift of the atherosclerotic aorta increases with lesion progression

Abstract: BackgroundAtherosclerosis severity-independent alterations in DNA methylation, a reversible and highly regulated DNA modification, have been detected in aortic atheromas, thus supporting the hypothesis that epigenetic mechanisms participate in the pathogenesis of atherosclerosis. One yet unaddressed issue is whether the progression of atherosclerosis is associated with an increase in DNA methylation drift in the vascular tissue. The purpose of the study was to identify CpG methylation profiles that vary with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 40 publications
2
67
0
Order By: Relevance
“…In the diabetic condition, it is now beginning to be understood how cardiovascular complications can be linked to changes in the epigenome, both through DNA methylation [91,97] and histone modifications [42]. Studies in diabetic skeletal muscle have also demonstrated how nuclear-encoded mitochondrial protein expression can be regulated through DNA methylation [58,74].…”
Section: Discussionmentioning
confidence: 99%
“…In the diabetic condition, it is now beginning to be understood how cardiovascular complications can be linked to changes in the epigenome, both through DNA methylation [91,97] and histone modifications [42]. Studies in diabetic skeletal muscle have also demonstrated how nuclear-encoded mitochondrial protein expression can be regulated through DNA methylation [58,74].…”
Section: Discussionmentioning
confidence: 99%
“…The identified locations have been mapped to genes with known roles in the vascular wall or atherosclerosis (55,56). Globally hypomethylated chromosomal DNA is widely present in atherosclerotic plaques (57).…”
Section: Dna Methylationmentioning
confidence: 99%
“…60 Consistently, recent follow-up uncovered many CpG loci in atherosclerotic plaques that increase in methylation with lesion progression. 61 …”
Section: Epigenetics and The Diabetic Vasculature: From Sites To Cytesmentioning
confidence: 99%